‘Globalization Strategies for an Indian Company in the pharmaceuticals industry: a firm and industry level analyses.’ - BAID, ARIHANT (2009)
This is an analysis of teh API sector of the pharmaceutical industry globally and how an organisation in india (an emerging market) can globalise thus letting it compete in the international marketplace.